2005
DOI: 10.1080/08039480510022927
|View full text |Cite
|
Sign up to set email alerts
|

Scandinavian forensic psychiatric practices – an overview and evaluation

Abstract: The Scandinavian countries share a social-democratic and humanistic view in that mentally disturbed offenders should not be punished or sentenced to prison if they are considered unaccountable for their actions. The countries differ, however, for example regarding referrals for medico-legal examinations. This article gives: 1) an overview of the Scandinavian forensic psychiatric practices regarding organization, legislation, resources and use of methods, and 2) a study of forensic psychiatric assessment as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
0
15
0
1
Order By: Relevance
“…The main tool for the forensic expert is the clinical interview (Grøndahl, 2005). It could be argued that the clinical interview is not a sufficient tool to achieve acceptable reliability among experts.…”
Section: Psychiatric Screening Reports 339mentioning
confidence: 99%
“…The main tool for the forensic expert is the clinical interview (Grøndahl, 2005). It could be argued that the clinical interview is not a sufficient tool to achieve acceptable reliability among experts.…”
Section: Psychiatric Screening Reports 339mentioning
confidence: 99%
“…It has also been suggested that experienced clinicians are more able than less experienced judges to know when they are most likely to be correct and most likely to be wrong (Garb, 1989). Basic knowledge about decision theory and willingness to obtain feedback on their work can reduce potential errors made by forensic experts (Grøndahl, 2005;Rabinowitz, 1994). As long as the expert witnesses are aware of the limitations of their expertise, we believe, as Garb (1992) states, that they will be able to provide valuable expert testimony for the courts.…”
Section: Discussionmentioning
confidence: 97%
“…The study did not address questions regarding the basis of the decision processes, that is, why and how the judgment processes differed between the groups. Research on forensic psychiatric and psychological expertise is rather scarce (Grøndahl, 2005;Wettstein, 2005). More knowledge on judgment processes within this field of expertise can yield valuable data on how experts actually process or Forensic Psychiatric Judgments 663 judge clinical vignettes in contrast to inexperienced lay persons.…”
mentioning
confidence: 99%
“…Offenders found “not legally accountable” are sentenced to compulsory treatment. It is the court's obligation to evaluate if an accused person is legally accountable and two forensic psychiatric experts are usually appointed to conduct a psychiatric evaluation. To what extent the report meets prerequisite formal requirements is evaluated by the Norwegian Board of Forensic Medicine, a part of the Norwegian Civil Affairs Authority.…”
Section: Breivik's Psychiatric Evaluationsmentioning
confidence: 99%